Queering Coupledom? Consensual Non-Monogamies in Finnish Online News 2017–2021 - Taivaloja, Nita; Alasuutari, Varpu (Foreningen Lambda Nordica, 2025)
In recent years, popular interest in consensual non-monogamy (CNM) – including swinging, open relationships, and polyamory – has grown steadily in Finland. Finnish online media has started to explore intimate practices in which individuals agree to engage in sexual and/or loving relationships with multiple partners. In this article, we analyze fifty-six human-interest stories on CNM from the five largest online news platforms in Finland, published between 2017 and 2021, to build an understanding of how media representations of CNM contribute to constructing or deconstructing mononormativity and couple-normativity in Finland. The study locates in the field of critical social psychology, draws from queer and feminist theories of non-normative intimacies and employs reflexive thematic analysis to examine how mono- and couple-normativities are regulated in institutional contexts and the ways online news shapes public knowledge, understanding, and attitudes. Our findings indicate that while media representations construct CNM as a valid and beneficial relationship option for some, underlying assumptions of mononormativity and couple-normativity remain strong.